Determination of Contents of Seven Heavy Metals in Chalk - Yu-Kui, Rui (Asian Journal of Chemistry, 2011)
The contents of seven heavy metals i.e., Cu, Pb, Hg, Cd,As, Mn and Cr in chalks were analyzed by ICP-MS. Correlation coefficients of detected elements range from 0.990-0.9999, limits of detection range from 0.08-0.56 μg/L and relative standard deviations range from 0.98-3.66 % for all elements. Results show that the heavy metal content of chalks is lower than road dusts, concentrations of Cu, Pb, Hg, Cd, As, Mn and Cr are 1.661, 0.649, 1.290, 0.043, 3.105, 11.775 and 0.819 μg/g, respectively. The data suggested that heavy metal pollution is not the main factor for chalk, but respiratory hazards should be paid more attention for teachers using chalk.